Synthesis of nano-magnetite from industrial mill chips for the application of boron removal: characterization and adsorption efficacy - Abba, Mohammed Umar; Che Man, Hasfalina; Azis, Raba’ah Syahidah; Idris, Aida Isma (MDPI AG, 2021)
The present study synthesized nano-magnetite (Fe3O4) from milled steel chips using the high energy ball milling (HEBM) method, characterized it, and then utilized it as a sorbent to remediate boron concentration at various pH (4–9), dosages (0.1–0.5 g), contact times (20–240 min), and initial concentrations (10–100 mg/L). The nano-sorbents were characterized based on SEM structure, elemental composition (EDX), surface area analysis (BET), crystallinity (XRD), and functional group analysis (FTIR). The highest adsorption capacity of 8.44 mg/g with removal efficiency of 84% was attained at pH 8, 0.5 g dosage, contact time of 180 min, and 50 mg/L initial concentration. The experimental data fit best with the pseudo-second-order kinetic model with R2 of 0.998, while the Freundlich adsorption isotherm describes the adsorption process with an R2 value of 0.9464. A regeneration efficiency of 47% was attained even after five cycles of reusability studies. This efficiency implies that the nano-magnetite has the potential for sustainable industrial application.